1983
DOI: 10.1073/pnas.80.15.4803
|View full text |Cite
|
Sign up to set email alerts
|

Expression of bacterial genes in plant cells.

Abstract: Chimeric bacterial genes conferring resistance to aminoglycoside antibiotics have been inserted into the Agrobacterium tumefaciens tumor-inducing (Ti) plasmid and introduced into plant cells by in vitro transformation techniques. The chimeric genes contain the nopaline synthase 5' and 3' regulatory regions joined to the genes for neomycin phosphotransferase type I or type II. The chimeric genes were cloned into an intermediate vector, pMON120, and inserted into pTiB6S3 by recombination and then introduced into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
238
0
11

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 728 publications
(250 citation statements)
references
References 47 publications
1
238
0
11
Order By: Relevance
“…Since identification of the Ti plasmid in Agrobacterium tumefaciens (Schell 1975) and development of the first genetically modified crop plant, an antibiotic-resistant tobacco plant (Fraley et al 1983), the public acceptance of genetically engineered plants has become a source of debate. Genetic engineering has been used successfully in J. regia since methods for somatic embryogenesis from immature cotyledons and plant regeneration were first developed (Tulecke and McGranahan 1985;McGranahan et al 1988McGranahan et al , 1990.…”
Section: Genetic Engineeringmentioning
confidence: 99%
“…Since identification of the Ti plasmid in Agrobacterium tumefaciens (Schell 1975) and development of the first genetically modified crop plant, an antibiotic-resistant tobacco plant (Fraley et al 1983), the public acceptance of genetically engineered plants has become a source of debate. Genetic engineering has been used successfully in J. regia since methods for somatic embryogenesis from immature cotyledons and plant regeneration were first developed (Tulecke and McGranahan 1985;McGranahan et al 1988McGranahan et al , 1990.…”
Section: Genetic Engineeringmentioning
confidence: 99%
“…Mary-Dell Chilton was the first to obtain a transgenic plant, but there were also two other leading groups in the field of plant genetic engineering. In early 1983, at a conference on genetic engineering in plants, Schell and Van Montagu (of the University of Ghent), Rob Horsch and Fraley (of Monsanto) and Chilton (from Washington University) all announced similar results: all three groups had successfully expressed antibiotic genes in plant cells (Newton, 2010;Fraley et al, 1983;Herrera-Estrella et al, 1983;Chilton, 2001). All three groups had set out to find a method for transferring genes to plants, and they had succeeded.…”
Section: Industry and Biotechnology In The Early Stages Of Transgenesismentioning
confidence: 93%
“…The APH(3')II activity migrated in non-denaturing polyacrylamide gels as two bands. The reason for this has not been defined, but it could obviously be due to post-translational modifications, proteolysis or association with other cellular protein(s) as previously found in animal cells (ColbereGarapin et al, 1981 , 1983bBevan et al, 1983;Fraley et al, 1983;Horsch et al, 1984;Murai et al, 1983). Experiments are now in progress to optimize the procedure for gene-mediated transformation of protoplasts.…”
Section: Introductionmentioning
confidence: 99%
“…In plants the only available method for genetic transformation is based on the ability of the soil bacterium Agrobacterium tumefaciens to transfer and to integrate part of its genetic material into genomic DNA (e.g., Bevan and Chilton, 1982). This complex natural transformation process has also been exploited for integrating functional foreign genes into the plant genome , 1983bBevan et al, 1983;Fraley et al, 1983;Horsch et al, 1984;Murai et al, 1983). Further, direct transformation of isolated Ti plasmid into protoplasts (Davey et al, 1980;Krens et al, 1982) has demonstrated that foreign DNA could be taken up by plant cells and integrated into the genome, but did not exclude the possibility that Ti plasmid-specific functions are essential for this transformation process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation